Reorienting fiscal policy: A critical assessment of fiscal fine-tuning - Pavlina R. Tcherneva (Levy Economics Institute of Bard College, 2013)
The present paper offers a fundamental critique of fiscal policy as it is understood in theory and exercised in practice. Two specific demand-side stabilization methods are examined here: conventional pump priming and the new designation of fiscal policy effectiveness found in the New Consensus literature. A theoretical critique of their respective transmission mechanisms reveals that they operate in a trickle-down fashion that not only fails to secure and maintain full employment but also contributes to the increasing postwar labor market precariousness and the erosion of income inequality. The two conventional demand-side measures are then contrasted with the proposed alternative - a bottom-up approach to fiscal policy based on a reinterpretation of Keynes's original policy prescriptions for full employment. The paper offers a theoretical, methodological, and policy rationale for government intervention that includes specific direct-employment and investment initiatives, which are inherently different from contemporary hydraulic fine-tuning measures. It outlines the contours of the modern bottom-up approach and concludes with some of its advantages over conventional stabilization methods.
Keywords: E24; E25; E62; E63; J68; 330; Full Employment; Fiscal Policy; Aggregate Demand; Business Cycles; Income Distribution; New Consensus